Isolation and worry in relation to gambling and onset of gambling among psychiatry patients during the COVID-19 pandemic: A mediation study - Forsström, David; Lindner, Philip; Månsson, Kristoffer N. T.; Ojala, Olivia; Hedman-Lagerlöf, Maria; El Alaoui, Samir; Rozental, Alexander; Lundin, Johan; Jangard, Simon; Shahnavaz, Shervin; Sörman, Karolina; Lundgren, Tobias; et al. (Frontiers in Psychology, 2022)
When the COVID-19 pandemic started spreading globally there was a fear that addictive behaviors would increase because of changes in everyday life caused by restrictions due to COVID-19. Studies were carried out to explore if this was true for gambling, typically revealing no overall increase in gambling behavior, although individuals who had previous experience of gambling problems were more likely to increase gambling during the pandemic. However, these studies only included individuals with previous gambling problems. It remains unknown whether other vulnerable groups, such as individuals with common mental disorder increased their gambling. The aims of this study were to explore the level of gambling problems among individuals with a history of mental disorder, namely (i) pre-pandemic gamblers, and (ii) pandemic-onset gamblers. Further, we explore if worry and isolation mediates gambling and problem gambling. The data was analyzed using descriptive statistics and a structural equation model to investigate mediation. Results showed a high prevalence of at-risk and problem gambling in both groups. The pre-pandemic gamblers had a high level of at-risk and problem gambling. Furthermore, the individuals that started to gamble during the pandemic had an even higher degree of at-risk and problem gambling. The mediation showed that onset of gambling was linked with worry of COVID-infection and that worry predicted the level of gambling problems. This study highlights that vulnerability factors, isolation and worry, can be triggers for individuals with common mental disorders to engage in gambling as well as the importance of screening this population for gambling problems.